Double‐Dose Versus Standard‐Dose Clopidogrel According to Smoking Status Among Patients With Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention - Bossard, Matthias (J Am Heart Assoc, 2017)
BACKGROUND: Prior Studies have suggested better outcomes in smokers compared with nonsmokers receiving clopidogrel (“smoker's paradox”). The impact of a more intensive clopidogrel regimen on ischemic and bleeding risks in smokers with acute coronary syndromes requiring percutaneous coronary interventions remains unclear. METHODS AND RESULTS: We analyzed 17 263 acute coronary syndrome patients undergoing percutaneous coronary intervention from the CURRENT‐OASIS 7 (Clopidogrel and Aspirin Optimal Dose Usage to Reduce Recurrent Events—Seventh Organization to Assess Strategies in Ischemic Symptoms) trial, which compared double‐dose (600 mg day 1;150 mg days 2–7; then 75 mg daily) versus standard‐dose (300 mg day 1; then 75 mg daily) clopidogrel in acute coronary syndrome patients. The primary outcome was cardiovascular death, myocardial infarction, or stroke at 30 days. Interactions between treatment allocation and smoking status (current smokers versus nonsmokers) were evaluated. Overall, 6394 patients (37.0%) were current smokers. For the comparison of double‐ versus standard‐dose clopidogrel, there were significant interactions in smokers and nonsmokers for the primary outcome (P=0.031) and major bleeding (P=0.002). Double‐ versus standard‐dose clopidogrel reduced the primary outcome among smokers by 34% (hazard ratio [HR] 0.66, 95% confidence interval [CI], 0.50–0.87, P=0.003), whereas in nonsmokers, there was no apparent benefit (HR 0.96, 95% CI, 0.80–1.14, P=0.61). For major bleeding, there was no difference between the groups in smokers (HR 0.77, 95% CI, 0.48–1.24, P=0.28), whereas in nonsmokers, the double‐dose clopidogrel regimen increased bleeding (HR 1.89, 95% CI, 1.37–2.60, P<0.0001). Double‐dose clopidogrel reduced the incidence of definite stent thrombosis in smokers (HR 0.41, 95% CI, 0.24–0.71) and nonsmokers (HR 0.63, 95% CI, 0.42–0.93; P for interaction=0.19). CONCLUSIONS: In smokers, a double‐dose clopidogrel regimen reduced major cardiovascular events and stent thrombosis after percutaneous coronary intervention, with no increase in major bleeding. This suggests that clopidogrel dosing in patients with acute coronary syndromes should be personalized, taking into consideration both ischemic and bleeding risk. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT00335452.